Study of Sick Building Syndrome (SBS) Prevalence in Hospitals and Other Health Care Centers Employees - M Abbaszadeh Ghanavati; E Jazayeri (Tehran University of Medical Sciences, 2008)
Background & Aim : Symptoms associated with acute discomfort, e.g., headache; eye, nose, or throat irritation; dry and itchy skin, which are known as Sick Building Syndrome (SBS) are well reported amongst people who work in hospital environment especially in the X- ray department. The aim of this study was to determine the prevalence of the symptoms and to identify work related factors in hospital environment.Materials and Methods : A questionnaire survey has been done from 219 hospital personnel who worked in the university hospitals (medical X-ray technologists, physiotherapists and office staff) as the exposed group and 219 personnel of the same occupations from private health care units and offices as the control group about if they experienced any of the mentioned symptoms in the last eight weeks. A total of 215 and 216 the questionnaire were accepted from each group respectively and included in analyses.Results: From data provided by this work, 6 symptoms (headache, sorethroat, sinusitis, dermatitis,nasalaids and sore eyes) have significant relationship between exposed and control groups. One symptom (catarrh) had significant difference among physiotherapists (P< 0.05), but with no significant difference between hospital and non-hospital environment. In addition, there was a relationship between incidence of dermatitis and history of skin allergy (P< 0.05).Conclusion: The results from this preliminary work are similar with the studies, which have been done by others. These results also suggest that there is a link between incidence of SBS and hospital based chemical agents.